Research on sustainable development of agricultural product cold chain logistics under public safety emergencies - He, Yuze; Liu, Mingfei (Frontiers in Sustainable Food Systems, 2023)
Under the sudden public security event, due to the characteristics of many participating subjects and wide distribution of space and time, the cold chain logistics of agricultural products is exceptionally vulnerable to impact, even causing interruption of logistics and affecting the regular order of life of residents. Thus, improving the resilience of agricultural cold chain logistics is highly urgent. This paper explores the process of the resilience of agricultural cold chain logistics under sudden public security events through rooting theory. Based on the knowledge metamodel, three elements of resilience event, resilience subject, and resilience measure are used to contextualize the resilience process. Finally, the Bayesian network and fuzzy set theory are used to create a contextual derivation model of agricultural cold chain logistics resilience under sudden public safety events. The research results show that the resilience process consists of the resistance, adaptation, readjustment, and innovation period, during which the government and enterprises jointly take measures to effectively resist the impact of sudden public events and further enhance the resilience of agricultural cold chain logistics through innovative development.